A cypovirus VP5 displays the RNA chaperone-like activity that destabilizes RNA helices and accelerates strand annealing. Issue 4 (5th December 2013) - Yang, Jie; Cheng, Zhenyun; Zhang, Songliu; Xiong, Wei; Xia, Hongjie; Qiu, Yang; Wang, Zhaowei; Wu, Feige; Qin, Cheng-Feng; Yin, Lei; Hu, Yuanyang; Zhou, Xi
Abstract: For double-stranded RNA (dsRNA) viruses in the family Reoviridae, their inner capsids function as the machinery for viral RNA (vRNA) replication. Unlike other multishelled reoviruses, cypovirus has a single-layered capsid, thereby representing a simplified model for studying vRNA replication of reoviruses. VP5 is one of the three major cypovirus capsid proteins and functions as a clamp protein to stabilize cypovirus capsid. Here, we expressed VP5 from type 5 Helicoverpa armigera cypovirus (HaCPV-5) in a eukaryotic system and determined that this VP5 possesses RNA chaperone-like activity, which destabilizes RNA helices and accelerates strand annealing independent of ATP. Our further characterization of VP5 revealed that its helix-destabilizing activity is RNA specific, lacks directionality and could be inhibited by divalent ions, such as Mg 2+, Mn 2+, Ca 2+ or Zn 2+, to varying degrees. Furthermore, we found that HaCPV-5 VP5 facilitates the replication initiation of an alternative polymerase (i.e. reverse transcriptase) through a panhandle-structured RNA template, which mimics the 5′-3′ cyclization of cypoviral positive-stranded RNA. Given that the replication of negative-stranded vRNA on the positive-stranded vRNA template necessitates the dissociation of the 5′-3′ panhandle, the RNA chaperone activity of VP5 may play a direct role in the initiation of reoviral dsRNA synthesis.